The evaluation of river maintenance - Morris, J.; Sutherland, D. C. (Cranfield University, 1993)
Rivers serve a variety of interests including those of water supply, drainage, environmental quality, and recreation. One of the main functions of managed rivers is to dispose of surplus water from urban and rural areas. In the case of rural areas this drainage function relates to the control, within acceptable limits, of flooding and water table levels on riparian, mainly agricultural land.